PHYSIOLOGICAL RESPONSE OF THE AQUATIC FERN Salvinia minima UNDER EXPOSURE TO METALS SUCH Pb, Ni, Cu, Zn AND Li - Gabriela Fuentes; Daniel Leal-Alvarado; Ignacio Fuentes-Franco; Tony Hoffmann; Claudia Kutter; David Uh-Ramos; Katiana Trejo; Neyi Estrella; Gerardo Carrillo-Niquete; Eduardo Gómez-Hernández; Jorge M Santamaría (Tropical and Subtropical Agroecosystems)
Background: Metals can be found in nature, but they are also generated by anthropogenic activities associated with technological waste, such as batteries and electronic components. These metals, when released to the environment may contaminate and cause significant health damage. Phytoremediation is a process to de-contaminate water bodies from metals using plants. Obviously, those plants should be able not only to uptake high amounts of metals, but also, they should be able to tolerate those high concentrations in their tissues.  Salvinia minima is a fast-growing, floating aquatic fern and its ability to take up metals from the environment has been evaluated. Objective: To characterize the physiological and molecular response of Salvinia minima plants exposed to different metals. Methodology: A system was designed to expose Salvinia minima plants to different metals such as Pb, Ni, Cu, Zn and Li, for seven days at different concentrations levels and take samples every 24 h. Various parameters were evaluated including metal uptake, metal concentration in the medium, leaf appearance, PSII efficiency (Fv/Fm), photosynthesis, transpiration, stomatal conductance. Results: S. minima plants were capable to accumulate Pb (28 mg /g DW at 40 uM), Zn (10 mg/g at 80uM) Li (10 mg/g at 20mM), Cu (8 mg/g at 40 uM) and Ni (4 mg/g at 40 uM), at their roots. At short times (0-24 h) and at low concentrations (of certain metals) no significant physiological damage was observed, however, at high concentrations or longer exposure times (48-144 h), physiological damage can be observed in terms of decreased photosynthesis and PSII efficiency, transpiration and stomatal conductance. Implications: Salvinia minima plant are capable to take Pb, Ni, Cu, Zn and Li from the medium, which indicates that it is a good candidate to be used in the phytoremediation of water bodies contaminated with these metals. Conclusions: Salvinia minima plants take up and accumulate high concentrations of Pb, Ni, Cu, Zn and Li in their tissues, thus reducing the metal content of aqueous media. Even though at high concentrations those metals may affect its physiological performance, this occurs at much higher concentrations than those normally found in natural water bodies, therefore S. minima is certainly a good candidate to be used for the phytoremediation of water bodies contaminated with metals.